THE EFFECT OF MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON THE VALUE OF MANUFACTURING COMPANIES - S. Syahyono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The value of the company that is formed can affect the investment received by a company. This study aims to examine the effect of the independent variables, namely managerial Ownership and Institutional Ownership, on firm value. This research will use a quantitative approach based on a sample of manufacturing companies listed on the Indonesia Stock Exchange from 2001 to 2014 totaling 110 companies, using the purposive sampling method. Meanwhile, the data analysis technique used for the examiners of this research is a statistical test using multiple linear regression. The study results show that the managerial ownership variable does not affect firm value, while the institutional ownership variable significantly affects substantial value.